TURATH WA TAJDID (THE STUDY OF THE IMPLEMENTATION OF THE MANAGEMENT INTEGRATIVE CURRICULUM IN EDUCATIONAL INSTITUTIONS OF THE ISLAMIC PERSPECTIVE OF HASSAN HANAFI) - Septiana Purwaningrum (Fenomena, 2022)
Teknologi yang semakin maju dan zaman yang terus berkembang menuntut lembaga pendidikan untuk survive dan mampu menjawab kebutuhan masyarakat. Sehingga dibutuhkan manajemen kurikulum yang bersifat futuristik namun tidak meninggalkan tradisi yang sudah baik. Kurikulum integratif dalam pendidikan menjadi salah satu solusi ideal dalam menjawab tantangan tersebut. Artikel ini bertujuan mendeskripsikan manajemen kurikulum integratif di SMA Trensains Tebuireng Jombang serta menganalisisnya perspektif pemikiran Hassan Hanafi. Artikel ini merupakan library research dan analisis datanya menggunakan teknik analisis isi. Hasil penelitian menunjukkan bahwa kepala SMA Trensains Tebuireng Jombang memiliki peran penting dalam fungsi manajemen kurikulum integratif, mulai dari perencanaan, pengorganisasian, pelaksanaan, pemberdayaan, pengawasan, hingga evaluasi. Manajemen kurikulum integratif di SMA Trensains yang disebut dengan Kurikulum Semesta relevan dengan pemikiran Hassan Hanafi. Kurikulum Semesta di lembaga ini sudah dilaksanakan dengan manajemen yang baik dan hasilnya membanggakan, dibuktikan dengan prestasi-prestasi yang diraih dalam banyak perlombaan sains di tingkat nasional. Berdasarkan hasil tersebut dapat disimpulkan bahwa seorang pemimpin lembaga pendidikan penting untuk mengintegrasikan tradisi dan modernitas untuk bisa survive. Turats tidak boleh menjadi barang mati yang hanya tersimpan di perpustakaan. Ajaran agama tidak boleh sekedar menjadi dogma. Kontekstualitas ajaran agama dengan modernitas menjadi sebuah keniscayaan untuk menyelenggarakan lembaga pendidikan Islam yang unggul dan kompetitif. Increasingly advanced technology and the age are constantly evolving demands of educational institutions to survive and answer the community's needs. So, it takes a futuristic management curriculum but does not leave the wonderful tradition. Integrative curriculum in education to be one of the ideal solutions in answering the challenge. This article aims to describe the management of an integrative curriculum in Trensains Senior High School Tebuireng Jombang and analyze the perspective of the thought of Hassan Hanafi. This article is library research and data analysis using content analysis techniques. The results showed that the Trensains Senior High School Tebuireng Jombang has a vital role in managing an integrative curriculum, including planning, organizing, implementing, empowerment, monitoring, and evaluation. Management integrative curriculum in Trensains Senior High School called with the curriculum of the universe relevant to the thought of Hassan Hanafi. The curriculum universe in this institution has been carried out with good management. The results are encouraging, evidenced by the achievements in many science races at the national level. Based on these results, it can be concluded that a leader of educational institutions is essential to integrate tradition and modernity to survive. Turats may not be dead, which is only stored in the library. The teachings of the religion should not simply be dogma. The context of the teachings of the faith with modernity becomes necessary to organize the educational institutions of Islam that are superior and competitive.